Implementing Smart Mobile Application to Achieve a Sustainable Campus - Zainal Rasyid Mahayuddin; Nur Afyfah Suwadi; Ruzzakiah Jenal; Haslina Arshad; Trio Adiono (International Journal of Supply Chain Management, 2018)
The use of technology nowadays is not an unusual matter especially in universities. The use of computer technology and the advanced networking that creates an integrated services and enables communication among the community of universities is a concept in a digital campus. However, in the education sector, the digital campus needs to be built as an essential foundation for the modernization of education and to facilitate a better campus life. This paper presents the concept and framework of Digital Campus as part of the universitys challenges in fostering an economical and socially sustainable campus. The implementation of co-created value in framework increases the efficiency of the digital campus concept. The use of mobile applications is very appropriate for achieving campus sustainability because of its increasing significant and ability. UKM Mobile Application as part of Digital Campus strategy is seen to be able to contribute to the sustainability of the campus. We also present the implementation of Digital Campus based on smart card usage in the applications such as attendance system, canteen payment and academic services. Mobile application development embedding value co-creation can improve the quality of service in terms of good communication with customers and the best services to the university.